1999
DOI: 10.1002/(sici)1096-9861(19990726)410:2<197::aid-cne3>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic axon terminals in the ventral tegmental area target a subpopulation of neurons expressing low levels of the dopamine transporter

Abstract: Cholinergic activation of dopaminergic neurons in the ventral tegmental area (VTA) is thought to play a major role in cognitive functions and reward. These dopaminergic neurons differentially project to cortical and limbic forebrain regions, where their terminals differ in levels of expression of the plasmalemmal dopamine transporter (DAT). This transporter selectively identifies dopaminergic neurons, whereas the vesicular acetylcholine transporter (VAchT) is present only in the neurons that store and release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
81
4
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 126 publications
(102 citation statements)
references
References 94 publications
14
81
4
3
Order By: Relevance
“…Cholinergic projections to the VTA come from brain stem nuclei, the pedunculopontine tegmental nucleus (PPTg) and the lateral dorsal tegmental nucleus (LDTg). Ultrastructural analyses have shown that cholinergic boutons within the VTA contact postsynaptic structures with low levels of dopamine transporter expression (Garzón et al, 1999). Numerous other neurotransmitters and neuromodulators influence the activity of the VTA, including serotonin, norepinephrine, endogenous opioids, and others (Tzschentke, 2001).…”
Section: Synaptic Transmission In the Mesoaccumbens Dopamine Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…Cholinergic projections to the VTA come from brain stem nuclei, the pedunculopontine tegmental nucleus (PPTg) and the lateral dorsal tegmental nucleus (LDTg). Ultrastructural analyses have shown that cholinergic boutons within the VTA contact postsynaptic structures with low levels of dopamine transporter expression (Garzón et al, 1999). Numerous other neurotransmitters and neuromodulators influence the activity of the VTA, including serotonin, norepinephrine, endogenous opioids, and others (Tzschentke, 2001).…”
Section: Synaptic Transmission In the Mesoaccumbens Dopamine Systemmentioning
confidence: 99%
“…Desensitization not only prevents further activation of nAChRs by nicotine, it also precludes the contribution of those nAChRs to endogenous cholinergic signaling. Cholinergic inputs to VTA from the laterodorsal and the pedunculopontine tegmental nuclei (Oakman et al, 1995) selectively target non-DA neurons and a subset of DA neurons (Garzón et al, 1999). VTA DA neurons are only sparsely targeted by cholinergic projections.…”
Section: Nicotinic Modulation Of Gabaergic Transmission In the Vtamentioning
confidence: 99%
See 2 more Smart Citations
“…Nicotine also activates then desensitizes α4β2-nAChRs on both DA and GABAergic neurons [9] . Since cholinergic innervations in GABAergic neurons have much higher density than that in DA neurons [11] , the nicotineinduced α4β2-nAChR desensitization (after brief activation) mainly decreases GABA release onto DA neurons, and consequently increases DA neuronal activity. It has been proposed that nicotine-induced desensitization is at least one of the major mechanisms for nicotine addiction [12][13][14] .…”
mentioning
confidence: 99%